The Theological Significance of Non-Chronological Qur'anic Stories: Moral Resonance in Strengthening the Da'wah Mission - Varzandeh, Mohsen; Dewi, Subkhani Kusuma (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
The narration of Qur'anic stories, which are identified as non-chronological, often leads to assertions about their function as advice and moral lessons, raising theological questions about their scientific nature. The way people understand these stories often focuses on their lessons and guidance, missing how they relate to the Prophet's da'wah. This study delves into the relationship between these narratives and their historical context, employing qualitative methods and drawing on the Sapir-Whorf Hypothesis, which suggests that language shapes our understanding of the world. Focusing on the narratives depicting the stories of the Prophets in Surah Hūd [11], the study reveals that the parts of these stories that emphasize the rejection of da'wah resonate with the experiences of Prophet Muhammad. The accounts of the rejected Prophets serve as a catalyst to ignite Prophet Muhammad's fervor for da'wah through the power of language. The portrayal of rejection in every da'wah struggle, accompanied by the narrative of punishment and annihilation, is distinctively crafted in the Qur'an, with a focus on punishment in the afterlife. The Prophet Muhammad's circumstances during the process of proselytizing are the primary factor in arranging the story fragments without chronological order.